Heat-resistant high-conductivity fiber-reinforced aluminum matrix composite core aluminum stranded wire and preparation method thereof
By depositing copper nanolayers on carbon fiber bundles and ultrasonic impregnation in aluminum alloy liquid, heat-resistant and highly conductive fiber-reinforced aluminum-based composite core aluminum stranded wires were prepared, which solved the problems of weight and unresistance of traditional strands, and achieved efficient conductivity and good core conductor compatibility.
Patent Information
- Application Number
- CN202510189153.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing steel core aluminum stranded wire has heavy weight, fiber polymer-based composite cores are not resistant to high temperatures, have poor conductivity, and have poor compatibility between core materials and conductors, making it difficult to meet the needs of efficient power transmission.
A carbon fiber bundle is used as the stranded core material, and heat-resistant, highly conductive fiber-reinforced aluminum-based composite core aluminum stranded wire is prepared through spiral stranding and copper plating. The method includes depositing copper nanolayers in a carbon fiber bundle and ultrasonic impregnation in a molten aluminum alloy liquid to form a multi-layer copper plating layer and a directionally solidified aluminum matrix micro-scale grain structure.
The heat resistance and conductivity of aluminum-based composite core aluminum stranded wires are improved, and the problems of heavy mass, unresistance to high temperatures and poor conductivity of traditional stranded wires are solved, and the compatibility between core materials and conductors is enhanced. It is suitable for long-distance power transmission and other high-performance needs.
Smart Images

Figure CN119852035A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials for power transmission lines, and in particular relates to a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire and a preparation method thereof. Background Art
[0002] With the vigorous development of my country's national economy, the demand for electricity continues to rise, which has put forward more stringent standards for the transmission capacity of transmission lines. At present, steel core stranded wire, as the key carrier for transmitting electric energy in traditional transmission lines, has exposed many drawbacks. However, the weight of steel core stranded wire itself is relatively large, which not only increases the load-bearing burden of infrastructure such as poles and towers, but also the chemical properties of steel make it very easy to electrochemical corrosion during use. This not only seriously affects the service life and power transmission safety of the conductor, but also brings many inconveniences to the installation and maintenance of the line due to its weight. At the same time, its relatively limited conductivity also limits the efficient transmission of electricity, making it difficult to meet the growing demand for electricity. In this context, in order to effectively deal with the above difficulties, various types of capacity-increasing conductors have emerged, in order to open up new ways to improve the transmission capacity and performance of transmission lines.
[0003] In the field of long-distance power transmission, high-end materials represented by continuous carbon fiber reinforced aluminum-based composite materials, which are characterized by light weight, high conductivity, high temperature resistance and electromagnetic shielding performance, make them an ideal choice for overhead wires. Compared with traditional steel-core aluminum stranded wires, continuous carbon fiber reinforced aluminum-based composite materials can not only reduce the load-bearing burden of poles and towers under the same conductivity, reduce construction costs and maintenance difficulties, but also reduce line losses and improve power transmission efficiency. In addition, in some special environments, such as areas with strong electromagnetic interference or high temperature areas, its advantages in electromagnetic shielding and high-temperature mechanical properties can be fully utilized to ensure the safe and stable operation of the power system and contribute key forces to the construction of a strong smart grid.
[0004] The prior art discloses a method for manufacturing a continuous alumina reinforced metal matrix composite material core for high temperature cables, wherein a continuous alumina fiber bundle and an aluminum conductor are used as core materials, the continuous alumina fiber bundle is in the middle, and the aluminum conductor is around the continuous alumina fiber bundle; the surface of the core material is wound with continuous alumina fibers in a spiral form to form a coating layer to obtain a coating material; the coating material is then compounded in molten aluminum liquid, and cooled to obtain the continuous alumina reinforced aluminum matrix composite material core. This process has a high heat resistance temperature, but the alumina fiber has a large density and low electrical conductivity.
[0005] In view of the problems that the steel core cable used for the current capacity-increasing conductor is heavy, the fiber-reinforced polymer-based composite material core is not resistant to high temperatures, and the core material has poor electrical conductivity, the present invention proposes a new heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire, which uses a carbon fiber bundle as the stranded wire core material and improves the heat resistance, core material conductivity and other properties through spiral twisting, copper plating and other methods.
[0007] In order to achieve the above purpose, the technical solution adopted is:
[0008] A method for preparing a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire comprises the following steps:
[0009] (1) depositing a copper nanolayer on the surface of the fiber filaments in the carbon fiber bundle by a coating process, and then performing ultrasonic immersion treatment in a molten aluminum alloy liquid to obtain an aluminum-based composite wire 1;
[0010] (2) depositing a copper nanolayer on the surface of the aluminum-based composite material wire 1 by a coating process to obtain an aluminum-based composite material wire 2;
[0011] (3) twisting the aluminum-based composite material wires 2 together to form an aluminum-based composite material strand 1;
[0012] (4) subjecting the aluminum-based composite material stranded wire 1 to ultrasonic immersion treatment in molten aluminum alloy liquid to obtain an aluminum-based composite material stranded wire 2;
[0013] (5) depositing a copper nanolayer on the surface of the aluminum-based composite material stranded wire 2 through a coating process to obtain an aluminum-based composite material stranded wire core material;
[0014] (6) The aluminum-based composite material stranded wire core material and aluminum wire are combined and twisted into a composite bundle to obtain the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire.
[0015] Furthermore, the carbon fiber bundle is a mesophase pitch-based carbon fiber, the diameter of the fiber bundle is 0.2-1.5 mm, and the thermal conductivity is 600-1100 W·m -1 ·K -1 、Conductivity is 0.8-1.5MS·m -1 ;
[0016] The diameter of the aluminum-based composite material wire material 1 is 0.2-2.8 mm, and its components by volume fraction are: 15-60% fiber and the rest aluminum.
[0017] Furthermore, the coating process in steps (1), (2) and (5) is physical vapor deposition, chemical vapor deposition, electroplating, solution deposition or spraying.
[0018] Furthermore, in the steps (1), (2) and (5), the thickness of the copper nanolayer is 50-100 nm.
[0019] Furthermore, in the steps (1) and (4), the temperature of the aluminum alloy liquid is 780-850° C., the ultrasonic immersion treatment power is 20-1000 W, the frequency is 10-30 kHz, and the time is 2-30 s;
[0020] Furthermore, in the steps (1) and (4), the aluminum alloy liquid includes the following components in weight percentage: Cu 1.5-4.5%, Ni 0.5-2.5%, Ti 0.5-1.5%, Zr 0.5-1.5%, Si 0.1-0.8%, Mg 0.1-1%, Sc0.1-0.8%, and the balance is Al.
[0021] Furthermore, in the step (3), a plurality of aluminum-based composite wires 2 of two diameters are spirally twisted to obtain an aluminum-based composite strand 1, and the twisted structure is 3+3 or 1×7+6;
[0022] The outer diameter d1 of the aluminum-based composite material stranded wire 1 is 1.2-12 mm, and the stranding pitch is S1=m×d1, wherein m is the pitch-to-diameter ratio, 10<m<25.
[0023] Furthermore, in the step (6), after the aluminum wire is arranged on the periphery of the aluminum-based composite material stranded wire core material, it is spirally twisted, and the twisting direction is consistent with the aluminum-based composite material stranded wire 1, and twisted into a composite bundle;
[0024] The diameter of the aluminum wire is 0.7-10 mm, the outer diameter d2 of the aluminum stranded wire with an aluminum-based composite material core is 1.5-25 mm, and the stranding pitch S2=m×d2, wherein m is the pitch-to-diameter ratio, 10<m<25.
[0025] Another inventive object of the present invention is to provide a heat-resistant and highly conductive fiber-reinforced aluminum-based composite core aluminum stranded wire, which is prepared by the above-mentioned preparation method and has a multi-scale nanostructure, namely, a micron structure between adjacent fiber filaments in a bundle, a micron structure between the nano-copper plating and the micron fiber filaments, a directionally solidified aluminum matrix micron-level grain structure, and an aluminum-based composite core with a millimeter-level structure. The multi-scale structural coupling can effectively improve the fracture failure mode and conductive performance of the continuous fiber-reinforced aluminum-based composite core aluminum stranded wire.
[0026] Another object of the present invention is to provide the application of the above-mentioned heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire in long-distance power transmission, aerospace electronics, and 3D printing raw materials.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention selects a high-conductivity intermediate phase asphalt-based carbon fiber reinforcement phase and a heat-resistant aluminum alloy matrix, and twists a plurality of continuous fiber-reinforced aluminum-based composite wires plated with a copper nanolayer into an aluminum-based composite strand according to a certain twisting structure and parameters (twisting pitch, pitch ratio, and outer diameter, etc.) and copper-plated. Then, the aluminum wire is used as the outer wire and the aluminum-based composite strand is used as the core material. The twisting parameters are controlled to achieve the preparation of heat-resistant and highly conductive fiber-reinforced aluminum-based composite core aluminum strand, thereby solving the problems of heavy weight of steel-core aluminum strands, poor conductivity of fiber polymer-based aluminum strands, and poor compatibility between core materials and conductors in the prior art. The advantages of the technical solution of the present invention are specifically as follows:
[0029] 1. The technical solution of the present invention utilizes the characteristics of continuous carbon fiber reinforced aluminum-based composite wire, such as strong thermal stability, high modulus, and excellent electrical conductivity, as the stranded wire core material, solving the problems of heavy steel core, high temperature resistance of fiber polymer-based core material, poor electrical conductivity, and poor compatibility between core material and conductor in the prior art.
[0030] 2. The technical solution of the present invention is to spirally twist continuous carbon fiber reinforced aluminum-based composite wires to form aluminum-based composite composite strands. Compared with a single metal-based composite wire as the strand core material, it solves the problem of brittle failure of fiber aluminum-based composite wires.
[0031] 3. The technical solution of the present invention comprises three layers of copper plating in the prepared aluminum-based composite material core aluminum stranded wire, which not only solves the problem that the composite material is easily corroded in a high temperature and high humidity environment, but also further improves the electrical conductivity of the aluminum-based composite material core aluminum stranded wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 (a) is continuous fiber reinforced aluminum matrix composite wire, (b) 3+3 twisted structure, (c) 1×7+6 twisted structure.
[0033] Figure 2 It is a schematic diagram of aluminum stranded wire with continuous fiber reinforced aluminum matrix composite core.
[0034] Explanation of the reference numerals: 1-aluminum matrix, 2-fiber filaments in carbon fiber bundles, 3-copper nanolayer, 4-stranded wire core aluminum matrix, 5-aluminum wire, 6-continuous fiber reinforced aluminum matrix composite strand. DETAILED DESCRIPTION
[0035] In order to further illustrate the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire and its preparation method of the present invention and achieve the intended purpose of the invention, the specific implementation method, structure, characteristics and efficacy of the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire and its preparation method proposed in accordance with the present invention are described in detail below in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0036] The following will further introduce in detail a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire and a preparation method thereof in conjunction with specific embodiments of the present invention:
[0037] The innovation of the present invention lies in: (1) using heat-resistant and highly conductive carbon fibers as the reinforcing phase and heat-resistant aluminum alloy as the metal matrix to form continuous fiber reinforced aluminum-based composite wires, thereby ensuring that the subsequent composite strands have the characteristics of heat resistance, high conductivity, and light weight. (2) The multi-layer copper nanolayer treatment not only further improves the conductivity of the composite strands, but also solves the corrosion damage to the strands by the external environment. (3) The continuous fiber reinforced aluminum-based composite wires are twisted according to a certain twisting structure to construct a spiral toughening structure, thereby reducing the risk of brittle fracture of the aluminum-based composite material. Therefore, the aluminum-based composite core aluminum stranded wire described in the present invention can provide technical support for the development of ultra-high voltage power cables for long-distance power transmission.
[0038] The technical solution of the present invention is:
[0039] A method for preparing a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire comprises the following steps:
[0040] (1) depositing a copper nanolayer on the surface of the fiber filaments in the carbon fiber bundle by a coating process, and then performing ultrasonic immersion treatment in a molten aluminum alloy liquid to obtain an aluminum-based composite wire 1;
[0041] (2) depositing a copper nanolayer on the surface of the aluminum-based composite material wire 1 by a coating process to obtain an aluminum-based composite material wire 2;
[0042] (3) twisting the aluminum-based composite material wires 2 together to form an aluminum-based composite material strand 1;
[0043] (4) subjecting the aluminum-based composite material stranded wire 1 to ultrasonic immersion treatment in molten aluminum alloy liquid to obtain an aluminum-based composite material stranded wire 2;
[0044] (5) depositing a copper nanolayer on the surface of the aluminum-based composite material stranded wire 2 through a coating process to obtain an aluminum-based composite material stranded wire core material;
[0045] (6) The aluminum-based composite material stranded wire core material and the aluminum wire are combined and twisted into a composite bundle to obtain the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire.
[0046] Furthermore, the carbon fiber bundle is a mesophase pitch-based carbon fiber, the diameter of the fiber bundle is 0.2-1.5 mm, and the thermal conductivity is 600-1100 W·m -1 ·K -1 、Conductivity is 0.8-1.5MS·m -1 ;
[0047] The diameter of the aluminum-based composite material wire material 1 is 0.2-2.8 mm, and its components by volume fraction are: 15-60% fiber and the rest aluminum.
[0048] In the above technical solution, the volume fraction of the components in the aluminum-based composite material wire 1 is limited. Since the thickness of the copper nanolayer is small, the copper nanolayer is ignored in this limitation.
[0049] Furthermore, the coating process in steps (1), (2) and (5) is physical vapor deposition, chemical vapor deposition, electroplating, solution deposition or spraying.
[0050] Furthermore, in the steps (1), (2) and (5), the thickness of the copper nanolayer is 50-100 nm.
[0051] Furthermore, in the steps (1) and (4), the temperature of the aluminum alloy liquid is 780-850° C., the ultrasonic immersion treatment power is 20-1000 W, the frequency is 10-30 kHz, and the time is 2-30 s.
[0052] Furthermore, in the steps (1) and (4), the aluminum alloy liquid includes the following components in weight percentage: Cu 1.5-4.5%, Ni 0.5-2.5%, Ti 0.5-1.5%, Zr 0.5-1.5%, Si 0.1-0.8%, Mg 0.1-1%, Sc0.1-0.8%, and the balance is Al.
[0053] In the above technical solution, the composition of the aluminum alloy liquid is a heat-resistant aluminum alloy, and the aluminum alloy of this composition can improve the high temperature resistance of the aluminum stranded wire with an aluminum-based composite material core.
[0054] Furthermore, in the step (3), a plurality of aluminum-based composite wires 2 of two diameters are spirally twisted to obtain an aluminum-based composite strand 1, and the twisted structure is 3+3 or 1×7+6;
[0055] The outer diameter d1 of the aluminum-based composite material stranded wire 1 is 1.2-12 mm, and the stranding pitch is S1=m×d1, wherein m is the pitch-to-diameter ratio, 10<m<25.
[0056] Furthermore, in the step (6), after the aluminum wire is arranged on the periphery of the aluminum-based composite material stranded wire core material, it is spirally twisted, and the twisting direction is consistent with the aluminum-based composite material stranded wire 1, and twisted into a composite bundle;
[0057] The diameter of the aluminum wire is 0.7-10 mm, the outer diameter d2 of the aluminum stranded wire with an aluminum-based composite material core is 1.5-25 mm, and the stranding pitch S2=m×d2, wherein m is the pitch-to-diameter ratio, 10<m<25.
[0058] In the above technical solution, the specific twisting method of steps (3) and (6) is defined, which can improve the strength of the product and avoid large gaps between different materials, thereby improving the performance of the final product.
[0059] The raw materials used in the present invention can all be purchased from the market, and each treatment not described in detail adopts a mature operating method in the prior art, which belongs to the common knowledge in the field.
[0060] Example 1.
[0061] The specific steps are as follows:
[0062] (1) A 50-100 nm thick copper nanolayer is deposited on the surface of the fiber filaments in two different diameters of carbon fiber bundles by using a coating process. The carbon fiber bundles are mesophase pitch-based carbon fibers with a diameter of 0.2-1.5 mm and a thermal conductivity of 600-1100 W·m -1 ·K -1 、Conductivity is 0.8-1.5MS·m -1 .
[0063] The coating process is physical vapor deposition, chemical vapor deposition, electroplating, solution deposition, or spraying.
[0064] Then, the treated continuous carbon fiber bundle is infiltrated into an aluminum alloy liquid at a temperature of 780-850°C, and the aluminum alloy liquid is infiltrated into the fiber bundle by means of power ultrasonic technology (power of 20-1000W, frequency of 10-30kHz, time of 2-30s). At the same time, based on the directional solidification induction effect, a columnar crystal structure is formed in the aluminum matrix, and the columnar crystal of the aluminum matrix solidifies and grows along the axial direction of the fiber to form a continuous carbon fiber reinforced aluminum-based composite wire with a diameter of 0.2-2.8mm, that is, the aluminum-based composite wire 1 (such as Figure 1 (as shown in (a)).
[0065] The aluminum alloy liquid includes the following components in weight percentage: Cu 1.5-4.5%, Ni 0.5-2.5%, Ti 0.5-1.5%, Zr 0.5-1.5%, Si 0.1-0.8%, Mg 0.1-1%, Sc 0.1-0.8%, and the balance is Al.
[0066] (2) A copper nanolayer with a thickness of 50-100 nm is deposited on the surface of the aluminum-based composite material wire 1 by the same coating process as in step (1), thereby obtaining an aluminum-based composite material wire 2.
[0067] (3) The two types of aluminum-based composite wires 2 with different diameters obtained in step (2) are spirally twisted to obtain an aluminum-based composite strand 1, and the twisted structure is 3+3 or 1×7+6. The outer diameter d1 of the aluminum-based composite strand 1 is 1.2-12 mm, and the twist pitch is S1=m×d1, where m is the pitch ratio, 10<m<25.
[0068] (4) The aluminum-based composite strand 1 obtained in step (3) is infiltrated into an aluminum alloy liquid at 780-850°C, and then the gaps in the strands are filled with the help of power ultrasonic technology (power is 20-1000W, frequency is 10-30kHz, and time is 2-30s), and an aluminum columnar crystal structure is formed under the induction of directional solidification to form a continuous fiber reinforced aluminum-based composite strand core material, i.e., the aluminum-based composite strand 2.
[0069] The aluminum alloy liquid includes the following components in weight percentage: Cu 1.5-4.5%, Ni 0.5-2.5%, Ti 0.5-1.5%, Zr 0.5-1.5%, Si 0.1-0.8%, Mg 0.1-1%, Sc 0.1-0.8%, and the balance is Al.
[0070] (5) A copper nanolayer with a thickness of 50-100 nm is plated on the surface of the aluminum-based composite strand 2 by the same coating process as in step (1), thereby obtaining a continuous fiber reinforced aluminum-based composite strand core material, i.e., an aluminum-based composite strand core material.
[0071] (6) The continuous fiber reinforced aluminum-based composite stranded wire core material in step (5) is combined with 8 bundles of aluminum wires with a diameter of 0.7-10 mm and twisted into a composite bundle. After the aluminum wires are arranged on the periphery of the aluminum-based composite stranded wire core material, they are spirally twisted, and the twisting direction is consistent with the aluminum-based composite stranded wire 1. The outer diameter d2 of the aluminum-based composite core aluminum stranded wire is 1.5-25 mm, and the twisting pitch S2 = m×d2, where m is the pitch-diameter ratio, 10<m<25.
[0072] Example 2.
[0073] The specific steps are as follows:
[0074] (1) A 100 nm thick copper nanolayer was deposited on the surface of the fiber filaments in the carbon fiber bundles with diameters of 0.2 mm and 0.7 mm respectively by PVD process. The carbon fiber bundles are mesophase pitch-based carbon fibers with a thermal conductivity of 900 W·m -1 ·K -1 , conductivity is 1.2MS·m -1 .
[0075] Then, the treated continuous carbon fiber bundle is infiltrated into an aluminum alloy liquid at a temperature of 800°C. With the help of power ultrasonic technology (power of 200 W, frequency of 18 kHz, and ultrasonic immersion time of 8 s), the aluminum alloy liquid is infiltrated into the fiber bundle. At the same time, based on the directional solidification induction effect, a columnar crystal structure is formed in the aluminum matrix. The columnar crystal of the aluminum matrix solidifies and grows along the axial direction of the fiber to form continuous carbon fiber reinforced aluminum-based composite wires with diameters of 0.4 mm and 1.3 mm, i.e., aluminum-based composite wires 1 (such as Figure 1 (as shown in (a)).
[0076] The aluminum alloy liquid includes the following components in weight percentage: Cu 3.5%, Ni 1.5%, Ti 1.5%, Zr 0.8%, Si 0.6%, Mg 0.3%, Sc 0.4%, and the balance is Al.
[0077] (2) A copper nanolayer with a thickness of 100 nm is deposited on the surface of the aluminum-based composite material wire 1 through a PVD coating process to obtain an aluminum-based composite material wire 2.
[0078] (3) The six bundles of aluminum-based composite wires 2 of two different diameters obtained in step (2) are twisted together according to a 3+3 twisting structure with a twisting pitch of 42 mm to form an aluminum-based composite strand 1 with a diameter of 2.8 mm. Figure 1 (b) as shown.
[0079] (4) The aluminum-based composite strand 1 obtained in step (3) is infiltrated into an aluminum alloy liquid at 800°C, and then the gaps in the strands are filled with the help of power ultrasonic technology (power is 200 W, frequency is 18 kHz, and ultrasonic immersion time is 8 s), and an aluminum columnar crystal structure is formed under the induction of directional solidification, forming a continuous fiber reinforced aluminum-based composite strand core material with a diameter of 3 mm, namely, the aluminum-based composite strand 2.
[0080] The aluminum alloy liquid includes the following components in weight percentage: Cu 3.5%, Ni 1.5%, Ti 1.5%, Zr 0.8%, Si 0.6%, Mg 0.3%, Sc 0.4%, and the balance is Al.
[0081] (5) A copper nanolayer with a thickness of 100 nm is plated on the surface of the aluminum-based composite strand 2 by a PVD coating process to obtain a continuous fiber reinforced aluminum-based composite strand core material, i.e., an aluminum-based composite strand core material.
[0082] (6) The continuous fiber reinforced aluminum-based composite stranded wire core material in step (5) is combined with 8 bundles of aluminum wires with a diameter of 2 mm to form a composite bundle with a twisting pitch of 144 mm to obtain a heat-resistant and highly conductive fiber reinforced aluminum-based composite material core aluminum stranded wire with a diameter of 7.2 mm, such as Figure 2 shown.
[0083] Example 3.
[0084] The specific steps are as follows:
[0085] (1) A 100 nm thick copper nanolayer was deposited on the surface of the fiber filaments in the carbon fiber bundles with diameters of 0.2 mm and 1.2 mm respectively by PVD process. The carbon fiber bundles are mesophase pitch-based carbon fibers with a thermal conductivity of 900 W·m -1 ·K -1 , conductivity is 1.2MS·m -1 .
[0086] Then, the treated continuous carbon fiber bundle is infiltrated into an aluminum alloy liquid at a temperature of 800°C. With the help of power ultrasonic technology (power of 200 W, frequency of 18 kHz, and ultrasonic immersion time of 8 s), the aluminum alloy liquid is infiltrated into the fiber bundle. At the same time, based on the directional solidification induction effect, a columnar crystal structure is formed in the aluminum matrix. The columnar crystal of the aluminum matrix solidifies and grows along the axial direction of the fiber to form continuous carbon fiber reinforced aluminum-based composite wires with diameters of 0.4 mm and 2.3 mm, namely, aluminum-based composite wires 1 (such as Figure 1 (as shown in (a)).
[0087] The aluminum alloy liquid includes the following components in weight percentage: Cu 3.5%, Ni 1.5%, Ti 1.5%, Zr 0.8%, Si 0.6%, Mg 0.3%, Sc 0.4%, and the balance is Al.
[0088] (2) A copper nanolayer with a thickness of 100 nm is deposited on the surface of the aluminum-based composite material wire 1 through a PVD coating process to obtain an aluminum-based composite material wire 2.
[0089] (3) The 13 bundles of aluminum-based composite wires 2 of two different diameters obtained in step (2) are twisted together according to a twisting structure of 1×7+6 (7 is an aluminum-based composite wire 2 with a larger diameter), with a twisting pitch of 105 mm, to form an aluminum-based composite strand 1 with a diameter of 7 mm, as shown in FIG. Figure 1 (c) as shown.
[0090] (4) The aluminum-based composite strand 1 obtained in step (3) is infiltrated into an aluminum alloy liquid at 800°C, and then the gaps in the strands are filled with the help of power ultrasonic technology (power is 200 W, frequency is 18 kHz, and ultrasonic immersion time is 8 s), and an aluminum columnar crystal structure is formed under the induction of directional solidification, forming a continuous fiber reinforced aluminum-based composite strand core material with a diameter of 7.2 mm, namely, the aluminum-based composite strand 2.
[0091] The aluminum alloy liquid includes the following components in weight percentage: Cu 3.5%, Ni 1.5%, Ti 1.5%, Zr 0.8%, Si 0.6%, Mg 0.3%, Sc 0.4%, and the balance is Al.
[0092] (5) A copper nanolayer with a thickness of 100 nm is plated on the surface of the aluminum-based composite strand 2 by a PVD coating process to obtain a continuous fiber reinforced aluminum-based composite strand core material, i.e., an aluminum-based composite strand core material.
[0093] (6) The continuous fiber reinforced aluminum-based composite stranded wire core material in step (5) is combined with 8 bundles of aluminum wires with a diameter of 5 mm to form a composite bundle with a twisting pitch of 420 mm to obtain a heat-resistant and highly conductive fiber reinforced aluminum-based composite material core aluminum stranded wire with a diameter of 17.5 mm, such as Figure 2 shown.
[0094] Example 4.
[0095] The specific steps are as follows:
[0096] (1) A CVD process was used to deposit a 80 nm thick copper nanolayer on the surface of the fiber filaments in the carbon fiber bundles with diameters of 0.3 mm and 1.2 mm, respectively. The carbon fiber bundles are mesophase pitch-based carbon fibers with a thermal conductivity of 1100 W·m -1 ·K -1 , conductivity is 1.5MS·m -1 .
[0097] Then, the treated continuous carbon fiber bundle is infiltrated into an aluminum alloy liquid at a temperature of 780°C. With the help of power ultrasonic technology (power of 1000 W, frequency of 30 kHz, and ultrasonic immersion time of 2 s), the aluminum alloy liquid is infiltrated into the fiber bundle. At the same time, based on the directional solidification induction effect, a columnar crystal structure is formed in the aluminum matrix. The columnar crystal of the aluminum matrix solidifies and grows along the axial direction of the fiber to form continuous carbon fiber reinforced aluminum-based composite wires with diameters of 0.7 mm and 2.5 mm, i.e., aluminum-based composite wires 1 (such as Figure 1 (as shown in (a)).
[0098] The aluminum alloy liquid includes the following components in weight percentage: Cu 1.5%, Ni 0.5%, Ti 0.5%, Zr 0.5%, Si 0.1%, Mg 0.1%, Sc 0.1%, and the balance is Al.
[0099] (2) A copper nanolayer with a thickness of 80 nm is deposited on the surface of the aluminum-based composite material wire 1 by a CVD coating process to obtain an aluminum-based composite material wire 2.
[0100] (3) The six bundles of aluminum-based composite wires 2 of two different diameters obtained in step (2) are twisted together according to a 3+3 twisting structure with a twisting pitch of 90 mm to form an aluminum-based composite strand 1 with a diameter of 6 mm. Figure 1 (b) as shown.
[0101] (4) The aluminum-based composite strand 1 obtained in step (3) is immersed in an aluminum alloy liquid at 780°C, and the gaps in the strands are filled with the help of power ultrasonic technology (power is 1000 W, frequency is 30 kHz, and ultrasonic immersion time is 2 s). Under the induction of directional solidification, an aluminum columnar crystal structure is formed to form a continuous fiber reinforced aluminum-based composite strand core material with a diameter of 8 mm, namely, the aluminum-based composite strand 2.
[0102] The aluminum alloy liquid includes the following components in weight percentage: Cu 1.5%, Ni 0.5%, Ti 0.5%, Zr 0.5%, Si 0.1%, Mg 0.1%, Sc 0.1%, and the balance is Al.
[0103] (5) A copper nanolayer with a thickness of 80 nm is plated on the surface of the aluminum-based composite strand 2 by a CVD coating process to obtain a continuous fiber reinforced aluminum-based composite strand core material, i.e., an aluminum-based composite strand core material.
[0104] (6) The continuous fiber reinforced aluminum-based composite stranded wire core material in step (5) is combined with 8 bundles of aluminum wires with a diameter of 6 mm and twisted into a composite bundle with a twisting pitch of 400 mm to obtain a heat-resistant and highly conductive fiber reinforced aluminum-based composite material core aluminum stranded wire with a diameter of 20 mm, such as Figure 2 shown.
[0105] Example 5.
[0106] The specific steps are as follows:
[0107] (1) A 50 nm thick copper nanolayer was deposited on the surface of the fiber filaments in the carbon fiber bundles with diameters of 0.5 mm and 1.5 mm respectively by electroplating. The carbon fiber bundles are mesophase pitch-based carbon fibers with a thermal conductivity of 600 W·m -1 ·K -1 、Conductivity is 0.8MS·m -1 .
[0108] Then, the treated continuous carbon fiber bundle is infiltrated into an aluminum alloy liquid at a temperature of 850°C. With the help of power ultrasonic technology (power of 20 W, frequency of 10 kHz, and ultrasonic immersion time of 30 s), the aluminum alloy liquid is infiltrated into the fiber bundle. At the same time, based on the directional solidification induction effect, a columnar crystal structure is formed in the aluminum matrix. The columnar crystal of the aluminum matrix solidifies and grows along the axial direction of the fiber to form continuous carbon fiber reinforced aluminum-based composite wires with diameters of 1 mm and 2.8 mm, that is, aluminum-based composite wires 1 (such as Figure 1 (as shown in (a)).
[0109] The aluminum alloy liquid includes the following components in weight percentage: Cu 4.5%, Ni 2.5%, Ti 1.2%, Zr 1.5%, Si 0.8%, Mg 1.0%, Sc 0.8%, and the balance is Al.
[0110] (2) A copper nanolayer with a thickness of 50 nm is deposited on the surface of the aluminum-based composite material wire 1 through an electroplating process to obtain an aluminum-based composite material wire 2.
[0111] (3) The 13 bundles of aluminum-based composite wires 2 of two different diameters obtained in step (2) are twisted together according to a twisting structure of 1×7+6 (7 is an aluminum-based composite wire 2 with a larger diameter), with a twisting pitch of 120 mm, to form an aluminum-based composite strand 1 with a diameter of 8 mm, as shown in FIG. Figure 1 (c) as shown.
[0112] (4) The aluminum-based composite strand 1 obtained in step (3) is infiltrated into an aluminum alloy liquid at 850°C, and the gaps in the strands are filled with the help of power ultrasonic technology (power is 20 W, frequency is 10 kHz, and ultrasonic immersion time is 30 s). Under the induction of directional solidification, an aluminum columnar crystal structure is formed to form a continuous fiber reinforced aluminum-based composite strand core material with a diameter of 10 mm, namely, the aluminum-based composite strand 2.
[0113] The aluminum alloy liquid includes the following components in weight percentage: Cu 4.5%, Ni 2.5%, Ti 1.2%, Zr 1.5%, Si 0.8%, Mg 1.0%, Sc 0.8%, and the balance is Al.
[0114] (5) A copper nanolayer with a thickness of 50 nm is plated on the surface of the aluminum-based composite strand 2 through an electroplating process to obtain a continuous fiber reinforced aluminum-based composite strand core material, namely, an aluminum-based composite strand core material.
[0115] (6) The continuous fiber reinforced aluminum-based composite stranded wire core material in step (5) is combined with 8 bundles of aluminum wires with a diameter of 8 mm and twisted into a composite bundle with a twisting pitch of 500 mm to obtain a heat-resistant and highly conductive fiber reinforced aluminum-based composite material core aluminum stranded wire with a diameter of 25 mm, such as Figure 2shown.
[0116] Example 6.
[0117] The performance of the conventional stranded steel core, fiber polymer composite core, the aluminum-based composite wire 2 in Example 2, and the two continuous fiber reinforced aluminum-based composite stranded wire cores in Example 2 and Example 3 were compared and analyzed, and the results are shown in Table 1.
[0118] Table 1 Comparison of comprehensive performance parameters
[0119]
[0120] From the results in Table 1, it can be seen that the electrical conductivity of aluminum-based composite wire material 2 and two continuous fiber-reinforced aluminum-based composite stranded wire core materials is greatly improved compared with the traditional stranded wire steel core and fiber resin-based composite core; the specific strength is increased by 70-76% and the density is reduced by about 70% compared with the traditional stranded wire steel core; the fracture toughness is increased by about 88% compared with the fiber polymer-based composite core, and the allowable use temperature reaches 450°C. It can be seen that the continuous carbon fiber reinforced aluminum-based composite stranded core of the present invention solves the problems of heavy weight of the traditional stranded wire steel core, the fiber polymer-based core material is not resistant to high temperature, and the electrical conductivity is poor.
[0121] In addition, fiber polymer-based composite materials are not suitable for the twisting method of the present invention because of their low fracture toughness and easy brittle fracture.
[0122] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.
Claims
1. A method for preparing a heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire, characterized in that: The following steps are involved: (1) depositing a copper nanolayer on the surface of the fiber filaments in the carbon fiber bundle by a coating process, and then performing ultrasonic immersion treatment in a molten aluminum alloy liquid to obtain an aluminum-based composite wire 1; (2) depositing a copper nanolayer on the surface of the aluminum-based composite material wire 1 by a coating process to obtain an aluminum-based composite material wire 2; (3) twisting the aluminum-based composite material wires 2 together to form an aluminum-based composite material strand 1; (4) subjecting the aluminum-based composite material stranded wire 1 to ultrasonic immersion treatment in molten aluminum alloy liquid to obtain an aluminum-based composite material stranded wire 2; (5) depositing a copper nanolayer on the surface of the aluminum-based composite material stranded wire 2 through a coating process to obtain an aluminum-based composite material stranded wire core material; (6) The aluminum-based composite material stranded wire core material and the aluminum wire are combined and twisted into a composite bundle to obtain the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire.
2. The preparation method according to claim 1, characterized in that: The carbon fiber bundle is a mesophase pitch-based carbon fiber, the diameter of the fiber bundle is 0.2-1.5 mm, and the thermal conductivity is 600-1100 W·m -1 ·K -1 、Conductivity is 0.8-1.5MS·m -1 ; The diameter of the aluminum-based composite material wire material 1 is 0.2-2.8 mm, and its components by volume fraction are: 15-60% fiber and the rest aluminum.
3. The preparation method according to claim 1, characterized in that: The coating process in steps (1), (2) and (5) is physical vapor deposition, chemical vapor deposition, electroplating, solution deposition or spraying.
4. The preparation method according to claim 3, characterized in that: In the steps (1), (2) and (5), the thickness of the copper nanolayer is 50-100 nm.
5. The preparation method according to claim 1, characterized in that: In the steps (1) and (4), the temperature of the aluminum alloy liquid is 780-850° C., the ultrasonic immersion treatment power is 20-1000 W, the frequency is 10-30 kHz, and the time is 2-30 s.
6. The preparation method according to claim 5, characterized in that: In the steps (1) and (4), the aluminum alloy liquid includes the following components in weight percentage: Cu 1.5-4.5%, Ni 0.5-2.5%, Ti 0.5-1.5%, Zr 0.5-1.5%, Si 0.1-0.8%, Mg 0.1-1%, Sc0.1-0.8%, and the balance is Al.
7. The preparation method according to claim 1, characterized in that: In the step (3), a plurality of aluminum-based composite wires 2 of two diameters are spirally twisted to obtain an aluminum-based composite strand 1, and the twisted structure is 3+3 or 1×7+6; The outer diameter d1 of the aluminum-based composite material stranded wire 1 is 1.2-12 mm, and the stranding pitch is S1=m×d1, wherein m is the pitch-to-diameter ratio, 10<m<25.
8. The preparation method according to claim 1, characterized in that: In the step (6), the aluminum wire is arranged on the periphery of the aluminum-based composite material stranded wire core material, and then spirally twisted, with the twisting direction being consistent with the aluminum-based composite material stranded wire 1, to form a composite bundle; The diameter of the aluminum wire is 0.7-10 mm, the outer diameter d2 of the aluminum stranded wire with an aluminum-based composite material core is 1.5-25 mm, and the stranding pitch S2=m×d2, wherein m is the pitch-to-diameter ratio, 10<m<25.
9. A heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Application of the heat-resistant and highly conductive fiber-reinforced aluminum-based composite material core aluminum stranded wire as described in claim 9 in long-distance power transmission, aerospace electronics, and 3D printing raw materials.
Citation Information
Cited By
Method for improving current-carrying capacity of power transmission aluminum conductor based on phosphoric acid electrochemical treatment
CN121496524A